Moroccan and Spanish agriculture comparative analysis 2008-2021 - Asllam, Lahoucine; Bari, Ahmed Ait; Amzil, Mustapha (Agriculture and Food Sciences Research, 2024)
In the general context of Morocco’s New Development Model, where public policies need all their credentials, and more specifically in the context of Morocco’s new agricultural strategy (Green Plan), the challenge is to develop modern agriculture with high added value and high productivity, capable of competing with agricultural production in other countries. This article compares the overall characteristics of agricultural production in Spain and Morocco. To make this comparative analysis, we have focused on a set of agricultural statistical aggregates, such as cultivated area, level of production and yield in relation to each family of agricultural products. These are calculated, using the Laspeyres index, over the period 2008 to 2021. In addition, we have chosen 2008 as the base year for plotting the evolution of Moroccan agricultural performance against that of Spain. The results of our comparative analysis showed that agriculture in Spain is more stable than in Morocco, particularly in cereals and fresh vegetables. Thus, they showed that the majority of Spanish agricultural products outperform those of Morocco. On the other hand, this comparative analysis showed that Moroccan agriculture outperforms Spanish agriculture in the production of sheep, apples, fresh peas, carrots, turnips, broad beans, green beans, goat meat, dried lentils and chickpeas, and that Moroccan agriculture outperforms Spanish agriculture in the production of dates and unshelled peanuts.